Attitude of dental interns toward learning communication skills in Bangalore city: A cross-sectional study - Shruti Ramesh; N Vanishree; M Anushri; V Chaithra; Deepa Bullappa; D S Pragathi (Wolters Kluwer Medknow Publications, 2018)
Background: Positive health outcomes are a result of effective physician-patient communication and assessment of the attitude of dental students toward learning communication skills may help dental educators to devise effective plans to orient students toward learning communication skills and make proactive efforts to hone their skills. Aims: The aim of this study is to assess the attitude of dental interns toward learning communication skills. Materials and Methods: A cross-sectional study involving 400 dental interns involving both males and females were selected from various dental colleges in Bangalore city for this study. Data were collected using the dental communication skills attitude scale, which consists of 24 items, 13 indicative of positive attitude and 11 indicative of the negative attitude toward learning communication skills. Statistical Analysis: The positive attitude scale and negative attitude scale scores were calculated and compared among different groups using SPSS software version 22. P < 0.05 was considered to be statistically significant. Results: Out of 400 participants, 150 (37.5%) were male and 250 (62.5%) were female. There was a significant difference in mean score of positive attitude between males (52.4 ± 5.6) and females (51.1 ± 6.0) (P = 0.03). The mean score of negative attitude was significantly higher among students whose teaching language was other than English (31.9 ± 5.1) when compared to students whose teaching language was English (29.8 ± 5.0) (P = 0.03). Conclusions: Dental interns have a strong positive attitude toward learning communication skills; however, negative attitudes should not be ignored, as they may subdue the importance of such programs.